2002
DOI: 10.1016/s0038-1098(02)00553-7
|View full text |Cite
|
Sign up to set email alerts
|

Sign of refractive index and group velocity in left-handed media

Abstract: We argue that the widely spread opinion that the left-handed media (LHM) are characterized by a negative refractive index n − is misleading. Since n does not enter into Maxwell's equations and boundary conditions, any medium may be described by both positive n and negative n − = −n.Two thermodynamic inequalities are presented, that make a difference between the LHM and the regular media (RM). The first one reads that the group velocity is positive in the RM and negative in the LHM. The second one is that the p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 12 publications
1
24
0
1
Order By: Relevance
“…Using thermodynamic arguments, it was shown that in a left-handed passive medium the real and imaginary parts of the index of refraction must have opposite signs [13]. This sign condition is not valid here since we deal with active media.…”
Section: 053601 (2006) P H Y S I C a L R E V I E W L E T T E R S mentioning
confidence: 93%
See 1 more Smart Citation
“…Using thermodynamic arguments, it was shown that in a left-handed passive medium the real and imaginary parts of the index of refraction must have opposite signs [13]. This sign condition is not valid here since we deal with active media.…”
Section: 053601 (2006) P H Y S I C a L R E V I E W L E T T E R S mentioning
confidence: 93%
“…Using typical values 10 8 Hz, 13 10 7 Hz, jd 34 j ' 10 ÿ29 Cm, and 12 ' B , negative permittivity and negative permeability at ÿ0:1 are obtained for a density N > 10 25 at=m 3 , which is perfectly realistic. Note that it is because we are interested in the vicinity of 12 0 that we need to choose !…”
Section: 053601 (2006) P H Y S I C a L R E V I E W L E T T E R S mentioning
confidence: 99%
“…[14]. It reads that the group velocity v g = ∂ω/∂k in an isotropic medium is positive in the regular …”
mentioning
confidence: 99%
“…On the other hand, in purely dielectric homogeneous media, negative dispersion is obtained only within the absorption bands. A homogeneous material can be simultaneously transparent and characterized by negative dispersion only if it has a nontrivial magnetic permeability 7,8 . Therefore, to obtain this result by homogenizing an intrinsically non-magnetic PC, one has to consider sufficiently large frequencies where the dispersion is negative 9 .…”
Section: Introductionmentioning
confidence: 99%